BIMODAL OXYGEN UPTAKE OF FRESHWATER AIR-BREATHING FEATHERBACK, NOTOPTERUS NOTOPTERUS (PALLAS) - KUMARI, RAGINI; ROY, PRABHAT K; GHOSH, TAPAN K. (Journal of the Inland Fisheries Society of India, 2021)
Oxygen uptake through gills and the swim bladder in relation to body weight have been measured in Notopterus notopterus at 24.5±1.0 ºC, using closed glass respirometer. With increase in body weight from 4.90 to 90.00 g, the rate of oxygen uptake per unit time (ml O2 h-1) increased from 1.520 to 4.113, 0.994 to 3.033 and 2.514 to 7.146 mlO2 h-1 through air, water and air+water respectively. The slope ‘b’ of the regression line for oxygen uptake per unit time in relation to body weight from air, water and total (air+water) were found to be 0.318, 0.403 and 0.350 respectively. The relationship has been found highly significant. The weight specific oxygen consumption in relation to body weight mlO2 kg-1 h-1 from air, water and air + water decreased from 309.750 to 45.700, 202.825 to 33.770 and 512.575 to 79.400 mlO2 kg–1 h–1 respectively with gradual increase in the body weight from 4.90 to 90.00 g. The log-log plot between the two variables gave straight lines with the slope ‘b’ of-0.618, -0.597 and-0.649 through air, water and air+water respectively. It has been estimated that a N. notopterus having average body weight of 29.01 g, extracted about 63% of oxygen from aerial route while only 37% through its aquatic route.Key words : Air-breathing fish, Notopterus notopterus, bimodal oxygen uptake